Diversity and Antimicrobial Resistance of Salmonella enterica Isolates from Surface Water in Southeastern United States - Li, Baoguang (American Society for Microbiology, 2014)
A study of prevalence, diversity, and antimicrobial resistance of Salmonella enterica in surface water in the southeastern United States was conducted. A new scheme was developed for recovery of Salmonella from irrigation pond water and compared with the FDA's Bacteriological Analytical Manual (8th ed., 2014) (BAM) method. Fifty-one isolates were recovered from 10 irrigation ponds in produce farms over a 2-year period; nine Salmonella serovars were identified by pulsed-field gel electrophoresis analysis, and the major serovar was Salmonella enterica serovar Newport (S. Newport, n = 29), followed by S. enterica serovar Enteritidis (n = 6), S. enterica serovar Muenchen (n = 4), S. enterica serovar Javiana (n = 3), S. enterica serovar Thompson (n = 2), and other serovars. It is noteworthy that the PulseNet patterns of some of the isolates were identical to those of the strains that were associated with the S. Thompson outbreaks in 2010, 2012, and 2013, S. Enteritidis outbreaks in 2011 and 2013, and an S. Javiana outbreak in 2012. Antimicrobial susceptibility testing confirmed 16 S. Newport isolates of the multidrug resistant-AmpC (MDR-AmpC) phenotype, which exhibited resistance to ampicillin, chloramphenicol, streptomycin, sulfamethoxazole, and tetracycline (ACSSuT), and to the 1st, 2nd, and 3rd generations of cephalosporins (cephalothin, amoxicillin-clavulanic acid, and ceftriaxone). Moreover, the S. Newport MDR-AmpC isolates had a PFGE pattern indistinguishable from the patterns of the isolates from clinical settings. These findings suggest that the irrigation water may be a potential source of contamination of Salmonella in fresh produce. The new Salmonella isolation scheme significantly increased recovery efficiency from 21.2 (36/170) to 29.4% (50/170) (P = 0.0002) and streamlined the turnaround time from 5 to 9 days with the BAM method to 4 days and thus may facilitate microbiological analysis of environmental water.